2016
DOI: 10.15282/ijleal.v4.481
|View full text |Cite
|
Sign up to set email alerts
|

Types of English Literature Teaching Approaches Preferred by Teachers in Secondary Schools in Miri, Sarawak

Abstract: This study aimed to investigate the types of literature teaching approaches preferably employed by Form 4 and Form 5 teachers who taught literature in English literature lessons in selected secondary schools in Miri, Sarawak. A mixed-method study was applied with the use of a questionnaire and interview questions. Three hypothesized relationships were tested with a sample of 43 trained teachers serving in seven urban secondary schools in Miri, Sarawak. Findings showed information-based approach was most prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…However, the findings also shown that the least preferred approaches out of the sixteen studies conducted on teaching approaches implemented by English teachers-two studies by Ling & Chen (2016) and Wahyuni et al (2021)-revealed that the two main approaches that are least preferred by teachers are the language-based approach and the paraphrastic approach. Therefore, it can be concluded that the other most preferred approach would be the other person's least preferred approach.…”
Section: Approaches Employed By Teachersmentioning
confidence: 90%
See 2 more Smart Citations
“…However, the findings also shown that the least preferred approaches out of the sixteen studies conducted on teaching approaches implemented by English teachers-two studies by Ling & Chen (2016) and Wahyuni et al (2021)-revealed that the two main approaches that are least preferred by teachers are the language-based approach and the paraphrastic approach. Therefore, it can be concluded that the other most preferred approach would be the other person's least preferred approach.…”
Section: Approaches Employed By Teachersmentioning
confidence: 90%
“…Sixteen articles were chosen to answer the RQ 1. And these ten studies by (Al Sabiri & Kaymakamoğlu, 2019;Atek et al, 2020;Bunga Febriani et al, 2022;Fauziah, 2016;Granath, 2017;Jabeen & Sarifa, 2022;Ling & Chen, 2016;Resueňo & Ian Bel Resueňo, 2019;Suliman et al, 2019;Wahyuni et al, 2021), revealed that there are six main approaches employed by teachers in teaching literature, which are the information-based approach, moral-philosophical approach, paraphrastic approach, language based approach, reader response approach, and stylistic approach. Subsequently, four studies by Benonguil & Barnido (2022); Hernández (2020); Moustafa & Naima (2022) and Yimwilai (2015) suggested other teaching methods such as the experimental group approach, communicative approach, affective responses approach, and focus group discussion.…”
Section: Approaches Employed By Teachersmentioning
confidence: 99%
See 1 more Smart Citation